First Principles Study on Electronic Structure and Optical Properties of Ternary GaAs:Bi Alloy - Yu, Lifei (Materials (Basel), 2012)
The electronic structure and optical properties of ternary GaAs:Bi alloy are investigated by first principles calculations. It is found that the band gap of GaAs(1-x)Bi(x) decreases monotonously with the increasing of Bi concentration, resulting in the fundamental absorption edge and main absorption peaks of GaAs(1-x)Bi(x) shifting toward lower energy with the increase of the Bi content. The optical constants of GaAs(1-x)Bi(x), such as the optical absorption coefficient, refractive index, extinction coefficient and optical conductivity, are greater than those of pure GaAs when x > 3.1%, but less than those of pure GaAs when x < 3.1%, which is primarily decided by the intraband level repulsions between Bi-induced states and host states on the valence bands; the contribution of Bi-6s, Bi-6p orbitals and Ga-4p, Ga-4s orbitals on conduction bands is also crucial. Bi doping plays an important role in the modulation of the static dielectric constant and the static refractive index. These results suggest a promising application of GaAs(1-x)Bi(x) alloy as a semiconductor saturable absorber.